1986
DOI: 10.1042/bj2390733
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of uridine(5′)-diphospho(1)-2,3-diacetamido-2,3-dideoxy-α-d-glucopyra nuronic acid from Pseudomonas aeruginosa P1-III

Abstract: A new uridine nucleotide was isolated from Pseudomonas aeruginosa P1-III (Habs serotype 5). On the basis of 13C-n.m.r. and p.m.r. spectroscopy, mass spectrometry, i.r.-absorption spectroscopy and circular dichrometry, the structure of the new compound was unequivocally identified as uridine(5')-diphospho(1)-2,3-diacetamido-2,3-dideoxy-alpha-D-gl ucopyranuronic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…ManNAc(3NAc)A, the C2-epimer of GlcNAc(3NAc)A, is present not only in the LPS of P. aeruginosa and B. pertussis , but also in the cell wall polysaccharide of the Gram-positive thermophile, Bacillus stearothermophilus 41 . GlcNAc(3NAc)A has been reported to be present in the LPS of a number of P. aeruginosa strains, including P1-III and P14, the N -linked glycans of the methanogenic archaea, Methanococcus voltae and Methanococcus maripalidus , and the cell surface polysaccharide of the Gram-negative spirochete, Treponema medium 42 43 44 45 . A partial genome research survey revealed that Thermus thermophiles ( Deinococcus-Thermus ), Zobellia galactanivorans ( Bacteroidetes ), Wolinella succinogenes ( Epsilonproteobacteria ) and Photorhabdus asymbiotica ( Gammaproteobacteria ) possess 5 genes in the Wbp pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ManNAc(3NAc)A, the C2-epimer of GlcNAc(3NAc)A, is present not only in the LPS of P. aeruginosa and B. pertussis , but also in the cell wall polysaccharide of the Gram-positive thermophile, Bacillus stearothermophilus 41 . GlcNAc(3NAc)A has been reported to be present in the LPS of a number of P. aeruginosa strains, including P1-III and P14, the N -linked glycans of the methanogenic archaea, Methanococcus voltae and Methanococcus maripalidus , and the cell surface polysaccharide of the Gram-negative spirochete, Treponema medium 42 43 44 45 . A partial genome research survey revealed that Thermus thermophiles ( Deinococcus-Thermus ), Zobellia galactanivorans ( Bacteroidetes ), Wolinella succinogenes ( Epsilonproteobacteria ) and Photorhabdus asymbiotica ( Gammaproteobacteria ) possess 5 genes in the Wbp pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These distinctive molecules have primarily been identified in the complex cell wall matrices of pathogenic bacteria and the glycoproteins of certain archaea. To date, GlcNAc(3NAc)A has been detected in the LPS of a number of P. aeruginosa strains, including P1−III and P14, and the unique N -linked glycans of the methanogenic archaea Methanococcus voltae and Methanococcus maripalidus . In addition to P. aeruginosa PAO1 (serotype O5), ManNAc(3NAc)A, the C2 epimer of GlcNAc(3NAc)A, is present in the LPS of other P. aeruginosa strains, as well as in the cell wall polysaccharide of the Gram-positive thermophile Bacillus stearothermophilus and the pathogens Bordatella pertussis , Bordatella parapertussis , and Bordatella bronchiseptica .…”
Section: Discussionmentioning
confidence: 99%
“…The 13 C data for UDP-GlcNAc at 10 mM (Table III) were obtained both directly by recording the one-dimensional 1 H -decoupled 13 C NMR spectrum and indirectly by the 1 Hdetected two-dimensional NMR analysis (data not shown). As C spectrum at high digitization.…”
Section: Evaluation Of the Structure Of Compound A By One-dimensionalmentioning
confidence: 99%
“…For instance, Okuda et al (13) have described the isolation and characterization of UDP-2,3-diacetamido-2,3-dideoxy-D-glucuronic acid from Pseudomonas aeruginosa P1-III, but its enzymatic synthesis was not studied. He and Liu (14) have described genes and enzymes for the biosynthesis of various 3-amino-3-deoxy-sugars.…”
mentioning
confidence: 99%